The synchronization of national policies : ethnography of the global tribe of moderns - Alasuutari, Pertti (Routledge advances in sociology, 2016)
The Synchronization of National Policies shows how it is possible that there is remarkable uniformity in the policies that the nation-states adopt, although there is no world government. Mainstream research attributes such global governance to the influence of leading countries, to functional requirements created by capitalism and technological development, or to international organizations. This book argues that to understand how national policies are synchronized we need to realize that the global population forms a single global tribe of moderns, divided into some 200 clans called nations. While previous research on the world culture of moderns has focused on the diffusion of ideas, this book concentrates on the active role of local actors, who introduce global models and domesticate them to nation-states. In national policymaking, actors justify new policies by international comparisons, by the successes and failures of models adopted in other countries, and by building and appealing to the authority of international organizations. Consequently, national policies are synchronized with each other. Yet, because of the way such domestication of global trends takes place, citizens retain and reproduce the understanding that they follow a sovereign national trajectory.
Keywords: International organization; State, The; Culture and globalization; politiikan sosiologia; kansallisvaltio; kansainväliset suhteet; diplomaattisuhteet; kansainvälinen politiikka; politiikka; United States : Foreign relations : Philosophy; Yhdysvallat